Implementation of Fuzzy Controller for ZCS Resonant Buck Converter Using Matlab/Simulink - Pidikiti, Tripura (International Journal of Advances in Applied Sciences, 2021)
Soft switching techniques are widely used to control dc-dc converters to increase the efficiency and power conversion density. In this paper, an auxiliary circuit to achieve the soft switching condition for a buck converter is presented. The switching devices used in power converters need to withstand high voltage stress across them which leads to increased switching losses. To maximize the efficiency, soft switching techniques must be adopted. The two popular soft switching techniques are Zero Voltage Switching (ZVS) and Zero Current Switching (ZCS). In this paper Zero Current Switching (ZCS) technique is used. The performance of the converter is analysed first with PID controller and then with fuzzy logic controller (FLC). Simulation results are presented on 60 W converter using MATLAB / SIMULINK and performance comparison is presented with PID and fuzzy controllers